DIGITAL QUEUE SYSTEM DESIGN BASED MIKROKONTROLER AT89S51 - Sapto Mujoko; Fivtatianti Hendajani, SKom., MM (Jurnal Sistem Komputer, 2009)
Series of "Design System Microcontroller Based Digital Queue AT89S51" functionto help create a safe, comfortable and orderly at the time of the queue for a particulartransaction. This tool is designed with Inputan a switch, the data processing usingAT89S51 Microcontroller IC, and output display and buzzer sevensegmen as anindicator of the number of queue detection. This tool works by detecting a pressureswitch Inputan, then microcontroller will process Inputan data input into the next willbe used to perform the counting process and the results will be displayed on theseven-segment indicator with buzzer that sounds. The seven segment displayfunctions provide information to visitors (queue) that the numbers that appear in thesevent-segment display shows the queue number that will make transactions